Analisa Laporan Kas Untuk Menilai Kinerja Keuangan Pemerintah Kabupaten Sukoharjo Tahun 2023-2024 - Ndandung Akbar Safii; Dika Puspitaningrum (International Forum of Researchers and Lecturers, 2026)
This study aims to assess the financial performance of the Sukoharjo Regency Government during the 2023-2024 period by employing cash flow statements as the primary analytical tool. Cash flow statements are considered essential as they provide a clear picture of liquidity conditions and the actual capacity of local governments to manage cash inflows and outflows. This research applies a descriptive quantitative approach using secondary data obtained from audited Budget Realization Reports and Cash Flow Statements. Financial performance is evaluated through revenue effectiveness ratios and expenditure efficiency ratios as key indicators of fiscal management. The results indicate that regional revenue realization consistently exceeded the established targets throughout the study period, placing revenue performance in the very effective category. This finding reflects the local government’s ability to maximize revenue potential during the post-pandemic economic recovery phase. However, the analysis of expenditure efficiency reveals that spending management has not yet reached an optimal level, as expenditure realization remained close to the allocated budget limits. These findings demonstrate that strong revenue performance does not necessarily correspond with efficient expenditure control. Consequently, local government financial performance should be evaluated comprehensively by integrating both revenue effectiveness and expenditure efficiency perspectives. This study contributes empirically to public sector accounting literature and offers practical insights for policymakers to strengthen budget control mechanisms and promote sustainable financial management at the regional level.